Mining-induced stress distribution of the working face in a kilometer-deep coal mine—a case study in Tangshan coal mine. (19th June 2018) - Xie, Jianlin; Xu, JiaLin; Wang, Feng
Abstract: Because of the large original stress in deep mining, compared with shallow mining, it is more likely to cause the occurrence of dynamic disasters such as rock burst, coal and gas outburst by the mining-induced stress concentration. Therefore, it is of great significance to master mining-induced stress distribution in deep mining. Mining-induced stress distribution of the working face in a kilometer-deep coal mine has been studied in this paper. The paper presents a study incorporating field monitoring, numerical simulation and theoretical analysis. Through analysis of field measured results, the following conclusions are made. For the area of the working face whose upward side and lateral direction are both unexcavated, the influence scope of advancing abutment pressure is 73 m; for another area whose upward side and lateral direction are both excavated, the influence scope is 64 m; for the area whose upward side is excavated and whose lateral direction is unexcavated, the influence scope is 31 m. Meanwhile, according to roadway displacement deformation monitoring, the influence scopes of advancing abutment pressure of the above areas are respectively 70 m, 68 m and 45 m, consistent with field stress monitoring results. In addition, the results obtained by FLAC 3D numerical simulation fits relatively well with field measured results. In the end, combining with theoretical analysis, it determines the high stress concentration zone of the working face, provides a decision-making basis for taking advanced pressure relief measures and offers a reference for the safe mining of both follow-up working faces and other working faces with similar conditions.